Geomechanical properties of mixtures of iron ore tailings improved with Portland cement - Oliveira, Tales Moreira de (2019)
This study aimed to use iron ore tailings in the construction of road pavements and embankments. To this end, it was investigated the geomechanical properties of mixtures of two iron ore tailings, improved with cement, whose results are important to characterize the behavior of mixtures regarding the mechanical actions imposed to the structural layer of paved roads. The results indicated that the studied tailings and mixtures without addition of cement presented uniform particle size, and despite having a CBR value that allows their application in sub-base layers, there would be the risk of other situations that compromise the mechanical behavior. However, with the addition of 5% cement, these mixtures showed behavior compatible for use in sub-base layers and embankments.